Life in the post-war Lithuanian SSR after escaping deportation - Laukaitytė, Regina (History / Istorija, 2019)
The article attempts to find out how the people who were trying to escape or managed to escape deportation in some way during the 1945–1953 Soviet deportations from Lithuania actually lived, how they were trying to hide and what steps were taken by the regime to expose and repress them. Statistical data, the motives and ways to escape deportation and the reasons of legalisation are analysed in the article. The policy of the Soviet regime, its capacities of organising additional deportations for those people who escaped deportation in the Lithuanian SSR and the operation of deporting such people entitled „Plus“, which was carried out in 1951–1952, are studied as well.